The Legal Protection For Applying Islamic Contract Law In Banking Regulation In Indonesia And Turkey - Dewi, Gemala (UI Scholars Hub, 2017)
This article discusses about the extent of readiness of the government regulation to meet the need of Islamic investment in the field of banking in Indonesia and Turkey, especially how legal protection to the banks and the customers in implementing sharia investment in both countries. This article is based on normative legal research, descriptive comparative through analysis the literature and regulatory provisions in force in the two countries. It is concluded that both Indonesia and Turkey have an arrangements of legislation and procedures in which guarantees the legal protection for every parties to apply islamic contract law through its secular legislation system. Depending on the customers would need to seek an appropriate mechanism in sharia based on freedom of contract. The difference is that in the legal systems being used also has differences, in which Indonesia has such a specific sources of law in which regulating the syariah principles. On the other hand Turkey does not.